Which health research gets used and why? An empirical analysis of 30 cases. Issue 1 (December 2016) - Kok, Maarten; Gyapong, John; Wolffers, Ivan; Ofori-Adjei, David; Ruitenberg, Joost
Abstract Background While health research is considered essential for improving health worldwide, it remains unclear how it is best organized to contribute to health. This study examined research that was part of a Ghanaian-Dutch research program that aimed to increase the likelihood that results would be used by funding research that focused on national research priorities and was led by local researchers. The aim of this study was to map the contribution of this research to action and examine which features of research and translation processes were associated with the use of the results. Methods Using Contribution Mapping, we systematically examined how 30 studies evolved and how results were used to contribute to action. We combined interviews with 113 purposively selected key informants, document analysis and triangulation to map how research and translation processes evolved and contributions to action were realized. After each case was analysed separately, a cross-case analysis was conducted to identify patterns in the association between features of research processes and the use of research. Results The results of 20 of the 30 studies were used to contribute to action within 12 months. The priority setting and proposal selection process led to the funding of studies which were from the outset closely aligned with health sector priorities. Research was most likely to be used when it was initiated and conducted by people who were in a position to use their results in their own work. The results of 17 out of 18 of these user-initiated studies were translated into action. Other features of research that appeared to contribute to its use were involving potential key users in formulating proposals and developing recommendations. Conclusions Our study underlines the importance of supporting research that meets locally-expressed needs and that is led by people embedded in the contexts in which results can be used. Supporting the involvement of health sector professionals in the design, conduct and interpretation of research appears to be an especially worthwhile investment.